A) C(-1,0) B) E(0,0) C) D(0,-1) D) A(0,1)
A) EA=1/2 B) EG=1 C) EF=1 D) FG=1
A) x+y2=1 B) x2-y2=1 C) x2+y=1 D) x2+y2=1
A) 4 cm B) 2 cm C) 1 cm D) 3 cm
A) 4 cm B) 2 cm C) 1 cm D) 3 cm
A) (x+1)2+(y+1)2=(3)2 B) (x-1)2+(y-1)2=(3)2 C) (x+1)2+(y-1)2=(3)2 D) (x+1)2+(y-1)2=(2)3
A) x2+y2=-1 B) x2+y2=1 C) x2-y2=1 D) x2.y2=1
A) Reemplazar el valor de "x" en la ecuación x2+y2=1. B) Reemplazar el valor de "x" en la ecuación x2+y2=1 y despejar "y". C) Reemplazar el valor de "x" y despejar "y". D) Reemplazar el valor de "x" en la ecuación x2+y=1 y despejar "y".
A) cot30°=1 B) tan30°=1 C) sen30°=1/2 D) cos30°=1/2
A) cotα=1/co B) cosα=ca/h C) tanα=co/ca D) senα=co/h |